The Potential Effect of Thymol from Black Seed Extract (Nigella Sativa) on Inhibiting the Growth of Candida albicans (Laboratory Studies in Leucorrhea Culture) - Thaariq, Nurul Aziza Ath; Hadisaputro, Suharyo; Supriyana, Supriyana (Indonesian Journal of Medicine, 2019)
Background: Leucorrhea is a complaint of reproductive health problems that are often experienced, 83% of cases are caused by Candida albicans. Candida albicans resistance to fluconazole (2.9%) and itraconazole (5.4%), so that antifungals from plant screening are safer and able to inhibit the growth of Candida albicans. This study aimed to explain the potential of thymol compounds in black cumin seed extract (Nigella sativa) various concentrations can inhibit the growth of Candida albicans.Subject and Method: This was a randomized controlled trial. The study sample was Candida albicans culture divided into 5 groups. The dependent variable was the growth of Candida albicans. The independent variable was thymol compounds of black cumin seed extract. The growth of Candida albicans was measured by calipers. The data were analyzed by one way ANOVA and post hoct.Results: Thymol 12.5% lowered the growth of Candida albicans 9.20 (mean= -9.20; p<0.001).Conclusion: Thymol compounds of black cumin seed extract has the potential as an alternative treatment for leucorrhea.Keywords: thymol, black seeds, Candida albicansCorrespondence:Nurul Aziza Ath Thaariq. Master of Applied of Midwifery, Health Polytechnics Ministry of Health Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Semarang 50239, Central Java. Email: naziza.aththaariq@gmail.com. Mobile: +6285869522220Indonesian Journal of Medicine (2019), 4(3): 285-292https://doi.org/10.26911/theijmed.2019.04.03.12